Persistence Conditions of Institutional Entities: Investigating Copredication Through a Forced-Choice Experiment - Murphy, Elliot (Frontiers in Psychology, 2021)
The conditions under which certain complex polysemous nominals can sustain coherent sense relations (informally, can “survive”) is investigated through a two-alternative forced choice experiment. Written scenarios were constructed which permitted copredication, through which multiple, semantically different sense types are associated with a single nominal. Participants were presented with two scenarios involving a polysemous nominal (e.g., bank, city) and had to select which scenario (and, hence, which combination of predicates) appeared to be the most prototypical, faithful realization of the nominal. In order to achieve this, an additional manipulation was added, such that the number of senses hosted by each forced choice was either equal (2 senses choice vs. 2 senses choice) or unequal (1 sense choice vs. 2/3 senses choice). In order to address certain concerns in the literature about prototypicality, a core question addressed was whether the institutional sense of the nominals strongly determined the option chosen by participants, or whether the number of senses more strongly predicted this. It was found that the best predictor of sense ‘survival’ was not sense frequency, but rather sense complexity or approximation to the institutional sense.